Physics-informed Platform for Flight Dynamics Simulation - Pattiwat Atayagul; Pitikhate Sooraksa (Sensors and Materials, 2025)
In this study, we present the state-of-the-art development of the flight dynamics model of a rigid body from the theoretical aspect of flight dynamics, design the software architecture, and validate the proposed architecture by comparing the simulation results with the check-cases for the verification of six-degree-of-freedom flight vehicle simulations document issued by the National Aeronautics and Space Administration (NASA).We also design the computational workflow between the ordinary differential equations of the system and other axillary components by weaving those relations in the object-oriented programing style and powered with Python scientific libraries.The simulation outcomes in all cases are well matched with the majority of NASA baseline datasets under the same flight simulation conditions, which reflect the accuracy of the model with considerable confidence.
Keywords: Aerospace and Aviation Technology; Model Reduction and Neural Networks; Numerical methods for differential equations